Messias Puer: Christian Knorr von Rosenroth's lost exegesis of kabbalistic Christianity - Knorr von Rosenroth, Christian (Aries book series, 2021)
Previously considered irretrievably lost, the discovery of the only manuscript of the Messias Puer composed by Knorr von Rosenroth, the leading exponent of Christian Kabbalah in the seventeenth century, gives us an important insight into the evolution of his thought and specific vision of the relations between Jews and Christians. Moreover, the subtle intertwining of both Kabbalah and the emerging biblical criticism at work in this partial commentary on the New Testament Gospels sheds new light on the largely unexplored role of Esotericism during the Modern Era in the construction of the future study of religion. This book includes a critical edition of the original manuscript and an annotated translation